2021
DOI: 10.1177/24705470211035607
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Psychological Flexibility Mediate Relationship Between Acute Psychedelic Effects and Decreases in Racial Trauma Symptoms Among People of Color

Abstract: Background Previous research showed acute psychedelic effects were associated with decreases in racial trauma (RT) symptoms among black, indigenous, and people of color (BIPOC). Among samples comprised primarily of white participants, positive outcomes of psychedelic experiences have been mediated by increases in psychological flexibility. Therefore, we examined whether changes in psychological flexibility from before to after a psychedelic experience mediated the relationship between acute psychedelic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 72 publications
(116 reference statements)
6
25
1
5
Order By: Relevance
“…All prior findings related to recalled decreases in racial trauma symptoms, alcohol use, depression, anxiety, and stress, as well as a significant recalled increase in psychological flexibility (AAQ) were replicated in this subsample (Davis, Xin, et al, 2021; Williams, Davis, et al, 2021; see ), despite a slight discrepancy in the participant sample.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…All prior findings related to recalled decreases in racial trauma symptoms, alcohol use, depression, anxiety, and stress, as well as a significant recalled increase in psychological flexibility (AAQ) were replicated in this subsample (Davis, Xin, et al, 2021; Williams, Davis, et al, 2021; see ), despite a slight discrepancy in the participant sample.…”
Section: Resultssupporting
confidence: 55%
“…In particular, the measure of ethnic identity was an abbreviated version of the MEIM (6 items), which may not have adequately captured the complexity and diversity of identities in the present sample. Additionally, as this sample was drawn from a larger pool of respondents (i.e., individuals having consumed all types of psychedelic substances), direct comparisons with the previously published findings in Williams, Davis, et al (2021) and Davis, Xin, et al (2021) cannot be made. We recommend that future surveys of this nature should include items capturing psychedelics used ceremoniously, comfort in disclosing ceremonial experiences, hesitancy in psychedelic research involvement due to past unethical practices, and/or information on use with members of one’s community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important principle of a context-dependent or relational approach to psychedelics is that the psychedelic experience itself is an important mediator of subsequent therapeutic outcomes – and there is much evidence to support this (Carbonaro et al, 2016; Carhart-Harris et al, 2016b; Davis et al, 2019, 2020, 2021b; Garcia-Romeu et al, 2015; Gasser et al, 2015; Griffiths et al, 2016, 2018; MacLean et al, 2011; Passie, 1997; Roseman et al, 2018; Ross et al, 2016; Schmid and Liechti, 2017). Specifically, a number of studies have found that ‘peak’ or ‘mystical’ – type experiences, which feature feelings of unity, transcendence of time, space and self, and positive mood, are predictive of subsequent positive therapeutic outcomes (Bogenschutz et al, 2015; Davis et al, 2019; Garcia-Romeu et al, 2015; Griffiths et al, 2016; Murphy et al, 2022; Pahnke, 1963; Roseman et al, 2018; Ross et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another salient dimension of the psychedelic experiences is the challenging experience (CE), which includes feelings of paranoia, anxiety, insanity and grief (Johnson et al, 2008). High ratings for CE have been associated with both worsened (Barrett et al, 2016; Carbonaro et al, 2016; Haijen et al, 2018; Roseman et al, 2018) and improved long-term mental health outcomes (Carbonaro et al, 2016; Davis et al, 2021b). These contradictory findings are likely explainable by whether a period of psychological challenge results in a psychological insightful therapeutic breakthrough or not (Barrett et al, 2016; Carbonaro et al, 2016; Davis et al, 2020; Roseman et al, 2018; Watts et al, 2017).…”
Section: Introductionmentioning
confidence: 99%